2004
DOI: 10.1002/ana.20101
|View full text |Cite
|
Sign up to set email alerts
|

Progressive age‐related development of Alzheimer‐like pathology in APP/PS1 mice

Abstract: Increasing evidence points to synaptic plasticity impairment as one of the first events in Alzheimer's disease (AD). However, studies on synaptic dysfunction in different transgenic AD models that overexpress familial AD mutant forms of amyloid precursor protein (APP) and/or presenilin (PS) have provided conflicting results. Both long-term potentiation (LTP) and basal synaptic transmission (BST) have been found to be both unchanged and altered in different models and under differing experimental conditions. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
223
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(255 citation statements)
references
References 69 publications
31
223
1
Order By: Relevance
“…Previous studies have reported that LTP is impaired in the hippocampus of various AD mouse models (9,(22)(23)(24). Here we used a mouse model of AD that expresses a mutated chimeric mouse/human APP and the exon-9-deleted variant of human PS1, both linked to familial AD, under the control of a prion promoter element (APPSwe/PS1dE9) (25).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that LTP is impaired in the hippocampus of various AD mouse models (9,(22)(23)(24). Here we used a mouse model of AD that expresses a mutated chimeric mouse/human APP and the exon-9-deleted variant of human PS1, both linked to familial AD, under the control of a prion promoter element (APPSwe/PS1dE9) (25).…”
Section: Resultsmentioning
confidence: 99%
“…20 The transgenic mouse model (APP/PS1) employed in this study expresses human APPs and PS1-ΔE9 and develops elevated Aβ1−42 levels at the age of 4 months with manifest plaque deposition a month later. 21 ψ-GSH (500 mg/kg ip) was administered to 3-month old APP/PS female mice three times per week for 12 consecutive weeks. Nontransgenic WT C57BL/6 mice were employed as negative controls.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…APP/PS1 mouse is a double transgenic mouse that overexpress APP together with presenilin 1 (PS1). These mice have an accelerated course of AD-like changes and currently are used by several laboratories for studies on the mechanisms of AD progression and for the development of new therapeutics (Trinchese et al, 2004). We demonstrated that social isolation rearing increases hippocampal Ab levels by increasing b-and g-secretase activities, resulting in the conversion of p35 to p25.…”
Section: Introductionmentioning
confidence: 81%